Approach in an adolescent Proteus male patient with megafoot - Derman, Orhan; Balci, Sevim; Engiz, Ozlem (The Turkish Journal of Pediatrics, 2008)
Proteus syndrome is a rare overgrowth syndrome characterized by hemihypertrophy, lower limb asymmetry, hyperpigmentations, lipomas, and vascular malformation. In this paper, we present a new adolescent Proteus syndrome patient with bilateral megafoot. He was very successful in playing football and was very popular among his friends. We present this case for the psychological and surgical aspects of this very interesting entity. We also review the recent literature related with Proteus syndrome.